New device permitting non‐invasive reversal of fetal endoscopic tracheal occlusion: ex‐vivo and in‐vivo study. (11th September 2020) - Basurto, D.; Sananès, N.; Verbeken, E.; Sharma, D.; Corno, E.; Valenzuela, I.; Van der Veeken, L.; Favre, R.; Russo, F. M.; Deprest, J.
ABSTRACT: Objective: One of the drawbacks of fetal endoscopic tracheal occlusion (FETO) for congenital diaphragmatic hernia is the need for a second invasive intervention to re‐establish airway patency. The 'Smart‐TO' device is a new balloon for FETO that deflates spontaneously when placed in a strong magnetic field, therefore overcoming the need for a second procedure. The safety and efficacy of this device have not yet been demonstrated. The aim of this study was to investigate the reversibility, local side effects and occlusiveness of the Smart‐TO balloon, both in a simulated in‐utero environment and in the fetal lamb model. Methods: First, the reversibility of tracheal occlusion by the Smart‐TO balloon was tested in a high‐fidelity simulator. Following videoscopic tracheoscopic balloon insertion, the fetal mannequin was placed within a 1‐L water‐filled balloon to mimic the amniotic cavity. This was held by an operator in front of their abdomen, and different fetal and maternal positions were simulated to mimic the most common clinical scenarios. Following exposure to the magnetic field generated by a 1.5‐T magnetic resonance (MR) machine, deflation of the Smart‐TO balloon was assessed by tracheoscopy. In cases of failed deflation, the mannequin was reinserted into a water‐filled balloon for additional MR exposure, up to a maximum of three times. Secondly, reversibility, occlusiveness and local effects of the Smart‐TO balloon were tested in vivo in fetal lambs. Tracheal occlusion was performed in fetal lambs on gestational day 95 (term, 145 days), either using the balloon currently used in clinical practice (Goldbal2) ( n = 5) or the Smart‐TO balloon ( n = 5). On gestational day 116, the presence of the balloon was assessed by tracheoscopy. Deflation was performed by puncture (Goldbal2) or MR exposure (Smart‐TO). Six unoccluded fetal lambs served as controls. Following euthanasia, the lung‐to‐body‐weight ratio (LBWR), lung morphometry and tracheal circumference were assessed. Local tracheal changes were measured using a hierarchical histologic scoring system. Results: Ex vivo, Smart‐TO balloon deflation occurred after a single MR exposure in 100% of cases in a maternal standing position with the mannequin at a height of 95 cm ( n = 32), 55 cm ( n = 8) or 125 cm ( n = 8), as well as when the maternal position was 'lying on a stretcher' ( n = 8). Three out of eight (37.5%) balloons failed to deflate at first exposure when the maternal position was 'sitting in a wheelchair'. Of these, two balloons deflated after a second MR exposure, but one balloon remained inflated after a third exposure. In vivo, all Smart‐TO balloons deflated successfully. The LBWR in fetal lambs with tracheal occlusion by a Smart‐TO balloon was significantly higher than that in unoccluded controls, and was comparable with that in the Goldbal2 group. There were no differences in lung morphometry and tracheal circumference between the two balloon types. Tracheal histology showed minimal changes for both balloons. Conclusions: In a simulated in‐utero environment, the Smart‐TO balloon was effectively deflated by exposure of the fetus in different positions to the magnetic field of a 1.5‐T MR system. There was only one failure, which occurred when the mother was sitting in a wheelchair. In healthy fetal lambs, the Smart‐TO balloon is as occlusive as the clinical standard Goldbal2 system and has only limited local side effects. © 2020 International Society of Ultrasound in Obstetrics and Gynecology